2015
DOI: 10.3389/fpsyg.2015.00566
|View full text |Cite
|
Sign up to set email alerts
|

Beauty and cuteness in peripheral vision

Abstract: Guo et al. (2011) showed that attractiveness was detectable in peripheral vision. Since there are different types of attractiveness (Rhodes, 2006), we investigated how beauty and cuteness are detected in peripheral vision with a brief presentation. Participants (n = 45) observed two Japanese female faces for 100 ms, then were asked to respond which face was more beautiful (or cuter). The results indicated that both beauty and cuteness were detectable in peripheral vision, but not in the same manner. Discrimina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 23 publications
0
25
0
Order By: Relevance
“…For example, Washburn et al (2014) collected body movement data in dance settings and found that trained dancers' WTC was significantly higher than that of non-dancers, indicating that dancers achieved a higher level of rhythmic coordination with their partners. WTC has also been applied to extract rhythmic convergence in a face-to-face, unstructured conversation (Fujiwara and Daibo 2016;Issartel et al 2015;Schmidt et al 2014). Fujiwara and Daibo (2016) observed significantly higher WTC values among genuine pairs who were engaged in actual conversation than among a pseudo pair that produced virtual data.…”
Section: Spectrum Analysis For Synchrony Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Washburn et al (2014) collected body movement data in dance settings and found that trained dancers' WTC was significantly higher than that of non-dancers, indicating that dancers achieved a higher level of rhythmic coordination with their partners. WTC has also been applied to extract rhythmic convergence in a face-to-face, unstructured conversation (Fujiwara and Daibo 2016;Issartel et al 2015;Schmidt et al 2014). Fujiwara and Daibo (2016) observed significantly higher WTC values among genuine pairs who were engaged in actual conversation than among a pseudo pair that produced virtual data.…”
Section: Spectrum Analysis For Synchrony Researchmentioning
confidence: 99%
“…The proportion of relative phase in nine 20° regions from 0° to 180° was also calculated. Following previous studies (e.g., Schmidt et al 2012), the region of 0°-20° was defined as in-phase patterning and the region of 160°-180° was defined as anti-phase patterning, and we targeted the area where the cross-wavelet spectrum was significant (Issartel et al 2015).…”
Section: Quantification Of Synchronymentioning
confidence: 99%
“…Following previous studies (Schmidt et al, 2012), the region of 0°-20°was defined as "in-phase patterning", while the region of 160°-180°was defined as "antiphase patterning". Since it was difficult to determine which frequency band should be focused on to extract the relative phase, the area in which the WTC was statistically significant was the subject of focus (Issartel, Bardainne, Gaillot, & Marin, 2015); the statistical significance level of the WTC was estimated using Monte Carlo methods (Grinsted et al, 2004). In this area, the number of occurrences in each 20°region was counted and the percentage distribution was calculated for each pair.…”
Section: The Present Studymentioning
confidence: 99%
“…Attractive faces were detected even at a relatively more peripheral location (i.e., 10˚of eccentricity from fixation), though the ability to perceive attractiveness for the same faces decreased (but still better than chance). Both beauty and cuteness appear to be detectable in peripheral vision, though the ability to judge cuteness may decline more in peripheral vision than for judging face beauty [41]. Thus, these few studies suggest that LSF information may be sufficient to appraise attractiveness and that important cues may be contained within the lower spatial frequencies and not confined to a specific higher SF band.…”
Section: Introductionmentioning
confidence: 96%